Spin-dependent radiative deflection in the quantum radiation-reaction regime. (14th January 2020) - Geng, X S; Ji, L L; Shen, B F; Feng, B; Guo, Z; Han, Q Q; Qin, C Y; Wang, N W; Wang, W Q; Wu, Y T; Yan, X; Yu, Q; et al.
Abstract: A new spin-dependent deflection mechanism is revealed by considering the spin-correlated radiation-reaction force during laser-electron collision. We found that such deflection originates from the non-zero work done by the radiation-reaction force along the laser polarization direction in each half-period, which is larger/smaller for spin-anti-paralleled/spin-paralleled electrons. The resulted anti-symmetric deflection is further accumulated when the spin-projection onto the laser magnetic field is reversed in adjacent half-periods. The discovered mechanism dominates over the Stern–Gerlach deflection for electrons of several hundreds of MeV and 10 PW-level laser peak power. The results provide a new perspective to study the strong-field QED physics in quantum radiation-reaction regime and an approach to leverage the study of radiation-dominated and strong-field QED physics via particle spins.